2008
DOI: 10.1007/s10439-008-9611-z
|View full text |Cite
|
Sign up to set email alerts
|

Digital Auscultation Analysis for Heart Murmur Detection

Abstract: This work presents a comparison of different approaches for the detection of murmurs from phonocardiographic signals. Taking into account the variability of the phonocardiographic signals induced by valve disorders, three families of features were analyzed: (a) time-varying & time-frequency features; (b) perceptual; and (c) fractal features. With the aim of improving the performance of the system, the accuracy of the system was tested using several combinations of the aforementioned families of parameters. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 30 publications
0
63
0
2
Order By: Relevance
“…The results obtained using the methods in DelgadoTrejos et al 8 and Quiceno-Manrique et al 18 were carried out using a subset of the database used in this study that did not contain diastolic murmurs. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained using the methods in DelgadoTrejos et al 8 and Quiceno-Manrique et al 18 were carried out using a subset of the database used in this study that did not contain diastolic murmurs. …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the results were compared with other assumed baseline methods in the literature. 8,23 The rest of this article is organized as follows: first, the time-varying representation implemented is introduced, followed by a brief description of the TVAR parameter estimation method used, computed by minimizing the mean-square error. Then, the methodology for feature extraction is described in detail (based on linear decomposition and partition schemes).…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents a complementary study of the methodology proposed in a previous work, 16 in witch t-f static features were compared with nonlinear and perceptual features using the same database of PCG signals. A major motivation in this work is to generate a set of time-varying feature contours, based on nonparametric TFR, and capable of representing the dynamics of the PCG signal integrating the t-f information present in the PCG signal.…”
Section: Introductionmentioning
confidence: 99%
“…Using a K-nearest neighbor's classifier they observed that fractal features provide the best accuracy (97, 17%) followed by spectral (95, 28%) and perceptual features (88,7%). This fact it is explained by the presence of long-range (fractal) correlation along with distinct classes of non-linear interactions [3]. The feature set described in our previous work [4] is a combination of time-frequency domain, perceptual and fractal analysis.…”
Section: Introductionmentioning
confidence: 99%